Influencing Factors on the Use of Antenatal Care in Bagmati Province, Nepal - Bohara, Pradeep Kumar; Devkota, Bijaya Mani; Sigdel, Uddhav (Educational Journal, 2026)
ANC shows a crucial role in improving maternal and neonatal health results, yet unequal access to ANC continues to be a problem in Nepal because of socio-economic and demographic disparities. This study analyzes the ANC determinants of ANC use in Bagmati Province based on data provided by Nepal Demographic and Health Survey. An analysis design based on the cross-sectional was used in a weighted sample of 468 women aged between 15 - 49 years who had live birth during the two years before the survey. Descriptive statistics (with survey weights) and logistic regression models were employed to determine the factors linked to ANC usage (at least once). All in all, ANC services were used by 87.6% of women, and 12.4% of them did not. The proportion of usage was greater among women aged 30-49 years (39.1%) than the proportion of under 20 (3.2%). Women with first parity had more ANC use (47.2%) as compared to those with third or higher birth order (13.1%). The urban women represented 77.7 percent of ANC users against 22.4 percent in the rural regions. There were also wealth inequalities as 40.8 percent of ANC users belonged to the richest quintile whereas only 9.9% belonged to the poorest. The multivariable analysis showed that the women who belonged to the wealthiest households (AOR = 14.65; 95% CI: 1.81118.64) and those who belonged to Bramhins/Chhetri ethnicity (AOR = 13.06; 95% CI: 2.7063.16) had a significantly higher likelihood The results indicate that there are significant socio-economic disparities in ANC use. Interventions must be targeted at poor women, rural women, and high-parity women to achieve equal access to maternal healthcare services in Nepal.